2021
DOI: 10.3390/ijerph18126530
|View full text |Cite
|
Sign up to set email alerts
|

Social Support for People with Morbid Obesity in a Bariatric Surgery Programme: A Qualitative Descriptive Study

Abstract: Background—Morbid obesity (MO) is a chronic metabolic disease affecting physical, psychological and social wellbeing. Bariatric surgery is a reliable method for losing weight in the long term, improving the quality of life, body image and social life of people with MO. Current literature recognises the importance of social support in controlling weight and coping with MO. The objective of this study was to describe and understand experiences related to social support for patients with MO included in a bariatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…The integration of support groups into bariatric pre-operative and post-operative care is therefore a recommendation for clinical practice to employ. [20][21][22] In addition to the social support required, guidelines on psychological therapy in bariatric surgery, 23 endorsed by the British Obesity Metabolic Surgery Society (BOMSS), recommend that all patients have a psychological screening assessment between 6 and 9 months post-surgery to identify the need for psychological intervention to mitigate poorer outcomes, such as eating disorders and mental illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of support groups into bariatric pre-operative and post-operative care is therefore a recommendation for clinical practice to employ. [20][21][22] In addition to the social support required, guidelines on psychological therapy in bariatric surgery, 23 endorsed by the British Obesity Metabolic Surgery Society (BOMSS), recommend that all patients have a psychological screening assessment between 6 and 9 months post-surgery to identify the need for psychological intervention to mitigate poorer outcomes, such as eating disorders and mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Research illustrates the beneficial impact communications with others ‘in a similar position’ to oneself can have on psychological wellbeing, e.g., 17–19 with communications with an individual who has undergone a medical procedure being associated with a reduction in anxiety and positive adjustment, with support groups often empowering individuals. The integration of support groups into bariatric pre‐operative and post‐operative care is therefore a recommendation for clinical practice to employ 20–22 …”
Section: Discussionmentioning
confidence: 99%
“…A past systematic review of 10 studies showed a positive correlation between social support and postoperative weight loss [ 9 ]. Additionally, the literature shows that apart from family, friends, and significant others, nurses and supportive staff are the most important pillar of social support for patients, given their frequent contact with the bariatric patients; the design of our group intends to take advantage of this close relationship, and is thus mainly run by our nurses, MAs, and dieticians [ 10 ]. Moreover, it seems that increasingly more groups are implementing eHealth interventions to improve post-bariatric surgery outcomes such as weight loss by increasing the social support of their patients; as shown by a recent systematic review of 17 studies, both eHealth intervention and control groups lost weight across the included studies, and eHealth approaches were found to be as effective or more effective than the control group in terms of weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Se observa, con base en las categorías AHRQ, que el 64,29% de los artículos fueron clasificados como nivel de evidencia VI. La Tabla 2 presenta un resumen de las características de los estudios incluidos (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) .…”
Section: Medline/pubmedunclassified
“…El estudio E3 se refiere a FB en el postoperatorio inmediato y el E4 muestra FB en el postoperatorio (12,7) . Los estudios E5, E6, E9 y E14 generalmente lo mencionan, mientras que los otros estudios: E7, E8, E10, E11, E12 y E13 no mencionan la CE (14)(15)(16)(17)(18)(19)22,23) .…”
Section: Medline/pubmedunclassified